Recent Development on Biodegradable Nanolubricant: A Review - Sathuramalingam, Pillay Darminesh; Nor Azwadi, Che Sidik; G., Najafi; R., Mamat; Tan, Lit Ken; Yutaka, Asako (Elsevier Ltd, 2017)
Naturally, biodegradable oil has better viscosity index, pour point, flash point, good tribology properties and its environmental friendly. Even though biodegradable lubricant is one of the best choice for lubrication purposes, however the properties are slightly lesser than mineral oil. A common solution for this problem is to provide effective additives into the base stock of biodegradable oil which leads to significant improvement to the lubricant by enhancing thermal properties, tribological properties and anti-oxidation capability. Nanoparticles are a type of effective additives which provides promising approach to enhance the biodegradable lubricant's properties. In this article, we reviewed the current progress and recently published data related to biodegradable lubricant, nanoparticles and its improvement on the biodegradable lubricant properties.